(untitled) (Research, Society and Development, 2022)
Autism spectrum disorder is a neurodevelopmental disorder characterized by atypical development, behavioral manifestations, deficits in communication and social interaction, repetitive and stereotyped behavior patterns. Among the different types of intervention, aspects of nutritional interventions will be addressed. Scientific literature has shown significant improvements and decreased symptoms, as most children have vitamin insufficiency, increased oxidative stress and reduced energy-carrying capacity. Some authors claim that gluten and casein cause a sensation of pleasure, in addition to hyperactivity, lack of concentration, irritability, difficulty in interacting with communication and sociability. This work aims to evaluate the importance of healthy eating for children with autism spectrum disorder. It is justified by the need to bring new discussions about food, of patients with this syndrome. This study was developed through a bibliographic survey through reading, research, compilations and collages of national authors, obtained through articles that address topics related to nutrition and autism.